Sparing Muscle Glycogen in Rats with Brown Sugarcane Supplementation - Kurnia Mar'atus Solichah; Suroto Suroto; Etika Ratna Noer (Universitas Airlangga, 2022)
ABSTRACT Background: Carbohydrates supplementation before exercise is known to delay fatigue in athletes, especially for endurance type of sports. Brown sugarcane (Saccharum officinarum) mostly contains sucrose. The breakdown of sucrose into glucose and fructose is used by the body as an energy-providing substrate, especially when exercising for a long duration – endurance. Consumption of brown sugarcane before exercise is expected to keep blood glucose in normal condition and preventing from muscle glycogen catabolism. Objectives: This research aimed to investigate the effect of carbohydrate supplementation with brown sugarcane and glucose on blood glucose and muscle glycogen levels. Methods: 36 male Sprague Dawley rats at 8 weeks old were involved in this study. There were 4 groups of intervention, brown sugarcane + swimming (BS), glucose + swimming (G), water + swimming (W), and brown sugarcane without swimming (S). The dose of intervention was 0,3 g sucrose/100 g body weight of rats. The supplementation was given 10 minutes before doing the swimming activity. A statistical test with SPSS software was used to analyze the results. One-way ANOVA and t-test were used to analyze before and after supplementation. Results: The results showed that the rats who were given sugar cane supplementation before swimming had a smaller increase in blood glucose than the other groups. The increasing of blood glucose in each group were BS = 7.95 mg/dl; G = 21.19 mg/dl; W = 35.64 mg/dl; S = 4.57 mg/dl; p=0.000. Muscle glycogen levels in the rats given sugar cane supplementation group were higher than in the other groups (p=0.000). Conclusions: Carbohydrate supplementation with brown sugarcane before endurance type of exercise was able to maintain blood glucose on normal condition and prevent muscle glycogen catabolism in experimental animals. Research on the development of sports spesific products based on brown sugarcane can be carried out to see its effects directly on humans. Keywords: brown sugarcane, glucose, glicogen, swimming, carbohydrates